Promoting Speaking Skill through Podcast: EFL Students’ Voices - Lutfa, Prasyifa Khabibatul; Kurniasih, Kurniasih; Fransiskus, Ferdinan (Nexus Publishing, 2024)
Listening is one of the skills in English Learning. Listening can be practiced by many media, like radio, audio music, listening while watching video, or listening to podcasts. Listening to podcasts is one of the popular and common ways to practice English listening skills. Listening to podcasts is simple and flexible to use every time everywhere, which makes many people like to listen to pod- casts. This study aims to investigate the use of podcasts for lis- tening strategies to improve speaking skills. 24 students partici- pated in this study from the University of Islam Malang in 2 and 4 grade in the English Department. The research design from this study uses data collection from a questionnaire involving 20 items scored 10 questions in yes or no choice and 10 questions scored on a five-point Likert response scale. Data analysis will be con- ducted using a descriptive approach, which to describe the find- ings from the questionnaire and identify patterns or trends that may emerge from students' responses to the use of podcasts in listening strategies. The results of this study indicate that the ma- jority of participants considered the use of podcasts as a listening strategy to improve speaking skills. Most of the participants of this study agreed that the podcast can help them and make it easier to listen skills comprehension, acquire new vocabulary, be- come accustomed to listening skills, and Improve speaking skills by practicing some content or accent in the podcast. Keywords: listening, podcast, speaking